Exploring C++: The Programmer’s Introduction to C++ - Lischner, Ray (Apress, 2012)
Each exploration in this book is a mixture of text and interactive exercises. The exercises are unlike anything you’ve seen in other books. Instead of multiple choice, fill-in-the-blank, or simple Q&A exercises, my lessons are interactive explorations of key C++ features. Early in the book, I will give you complete programs to work with. As you learn more C++, you will modify and extend programs. Pretty soon, you will write entire programs on your own. By “interactive,” I mean that I ask questions and you answer them. I do my best to respond to your answers throughout the lesson text. It sounds crazy, but by answering the questions, you will be learning C++. To help ensure you answer the questions, I leave space in this book for you to write your answers. I’m giving you permission to write in this book (unless you are borrowing the book from a library or friend). In fact, I encourage you to write all your answers in the book. Only by answering the questions will you learn the material properly. Sometimes, the questions have no right answer. I pose the question to make you ponder it, perhaps to look at a familiar topic from a new perspective. Other times, the question has an unambiguous, correct answer. I always give the answer in the subsequent text, so don’t skip ahead! Write your answer before you continue reading. Then and only then can you check your answer. Some questions are tricky or require information that I have not yet presented. In such cases, I expect your answer to be wrong, but that’s okay. Don’t worry. I won’t be grading you. (If you are using this book as part of a formal class, your teacher should grade this book’s exercises solely on whether you complete them, and never on whether your answer was correct. The teacher will have other exercises, quizzes, and tests to assess your progress in